Review Article: Pharmacological Activities and Bioactive Potential of Chinese Betel Leaf (Peperomia pellucida L. (Kunth.)) - Razoki, Razoki; Lister, INE; Mutia, Maya Sari (Journal of Pharmaceutical and Sciences, 2025)
Background: Peperomia pellucida L. Kunth (sirih cina) is a traditional medicinal plant used to treat various ailments. Its broad pharmacological potential needs to be consolidated from various publications to provide a comprehensive overview. Objective: This review aims to analyze and synthesize recent scientific evidence on the pharmacological activities, bioactive compounds, and potential applications of Pperomia pellucida. Methods: This systematic review was conducted by searching electronic databases (Google Scholar, PubMed, ScienceDirect, Scopus) using relevant keywords. From the search results, 21 original research articles published between 2015-2025 that met the inclusion criteria were analyzed descriptively and qualitatively. Results: The analysis revealed that Peperomia pellucida possesses diverse pharmacological activities, including anti-inflammatory, antibacterial, antifungal, antioxidant, anticancer, antidiabetic, antihypercholesterolemic, and osteogenic effects. These activities are supported by bioactive compounds such as flavonoids, tannins, alkaloids, and saponins. Its ethanolic extract has proven effective in in vitro and in vivo tests, including in topical formulations like creams and acne serums. Preliminary safety profiles indicate non-toxic properties. Conclusion: Peperomia pellucida shows great potential as a natural raw material for developing herbal medicines and cosmetics. Further research, such as human clinical trials and the development of technology-based formulations, is necessary to ensure its long-term safety and efficacy.